2016
DOI: 10.1371/journal.pone.0150641
|View full text |Cite
|
Sign up to set email alerts
|

Benzene Uptake and Glutathione S-transferase T1 Status as Determinants of S-Phenylmercapturic Acid in Cigarette Smokers in the Multiethnic Cohort

Abstract: Research from the Multiethnic Cohort (MEC) demonstrated that, for the same quantity of cigarette smoking, African Americans and Native Hawaiians have a higher lung cancer risk than Whites, while Latinos and Japanese Americans are less susceptible. We collected urine samples from 2,239 cigarette smokers from five different ethnic groups in the MEC and analyzed each sample for S-phenylmercapturic acid (SPMA), a specific biomarker of benzene uptake. African Americans had significantly higher (geometric mean [SE] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
5
16
0
Order By: Relevance
“…We and others have previously shown that GSTT1 null status has a strong effect on levels of SPMA (26, 27), and that was also observed in this study, where levels of SPMA were significantly lower in GSTT1 null individuals than in non-nulls (Table 3). The 95.4% increase in SPMA in these individuals may be due to PEITC effects on GSTP1 , which is a good catalyst of SPMA formation from benzene oxide (28).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We and others have previously shown that GSTT1 null status has a strong effect on levels of SPMA (26, 27), and that was also observed in this study, where levels of SPMA were significantly lower in GSTT1 null individuals than in non-nulls (Table 3). The 95.4% increase in SPMA in these individuals may be due to PEITC effects on GSTP1 , which is a good catalyst of SPMA formation from benzene oxide (28).…”
Section: Discussionsupporting
confidence: 90%
“…The analyses for the mercapturic acids were carried out essentially as described previously (21, 22). The limits of quantitation were 0.15 pmol/ml for SPMA, 20 pmol/ml for HPMA, and 12 pmol/ml for HMPMA.…”
Section: Methodsmentioning
confidence: 99%
“…These results correlate with the high lung cancer risk of African Americans and low lung cancer risk of Japanese Americans as compared to Whites, suggesting that BD could play a role in the differences in lung cancer etiology seen between these groups (3). Interestingly, a similar trend was recently reported for mercapturic acids derived from acrolein, crotonaldehyde, and benzene (51,61). Furthermore, levels of the mercapturic acid formed from benzene were strongly influenced by GSTT1 deletion, highlighting the important role of this GST gene in the detoxification of structurally distinct carcinogens (61).…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, a similar trend was recently reported for mercapturic acids derived from acrolein, crotonaldehyde, and benzene (51,61). Furthermore, levels of the mercapturic acid formed from benzene were strongly influenced by GSTT1 deletion, highlighting the important role of this GST gene in the detoxification of structurally distinct carcinogens (61). …”
Section: Discussionsupporting
confidence: 86%
“…This is a situation where biomarkers studies might provide insight into the tobacco smoke chemicals that are contributing to the adverse birth outcomes. For example, GSTT1 null genotype influences the levels of urinary benzene and 1,3-butadiene metabolites in smokers [22,23]. CYP1A1 and GSTT1 variants affect metabolite levels of a model polycyclic aromatic hydrocarbon, phenanthrene [24,25].…”
Section: Adverse Health Outcomesmentioning
confidence: 99%